Penetración y fortalecimiento del mecanismo de desarrollo limpio y las oportunidades del mercado del carbono para Colombia (2011)
This document, as part of a first phase of the project in question, seeks to answer two questions: i) Are there oppor- tunities in the regulated carbon market is not taking advantage of Colombia? and ii) What will happen to the carbon regulated market after 2012? It presents a framework of climate change and compile policy and technical bases of the Clean Development Mechanism, CDM. The study also includes a review of the state of the art of the CDM in Colombia, contextualizing this reality with other countries in the region, and summarizes the regulated market projections for the development of these projects. From these findings, we develop the foundations for the development of strategies to strengthen, penetration and diffusion of such projects in different sectors Colombians.